The Heterogeneity of Longitudinal Cognitive Decline in Euthymic Bipolar I Disorder With Clinical Characteristics and Functional Outcomes - Chen, Wen-Yin; Huang, Ming-Chyi; Lee, Ya-Chin; Chang, Chiao-Erh; Lin, Shih-Ku; Chiu, Chih Chiang; Liu, Hsing-Cheng; Kuo, Chian-Jue; Weng, Shih-Han; Chen, Po-Yu; Kuo, Po-Hsiu (Frontiers in Psychiatry, 2021)
We characterized the heterogeneity and risk factors of cognitive declines in euthymic bipolar disorder (BD), and their magnitude of associations with subjective daily functions. In this retrospective cohort, BD type I patients (N=128) were followed for an average of 6.5 years. Intelligence quotient (IQ) at index date was recorded, and premorbid IQ was estimated. We used Brief Assessment of Cognition in Affective Disorders (BAC-A) to assess cognition at follow-up. We evaluated current functions with World Health Organization Disability Assessment Schedule 2.0. Clinical and sociodemographic factors were examined for their independent effects on longitudinal cognitive declines. In addition, we employed multivariate adaptive regression spline to detect inflection points for the nature of slope changes in cognitive decline among BD patients. During follow-up years, 21 BD patients (16.4%) showed longitudinal cognitive declines. In cognitive declines group, all cognitive domains of BAC-A were significantly worsened. We found that density of episodes with psychotic features was an independent risk factor for cognitive declines after adjusted for age, gender and dose of mood stabilizer. After the age of 42 years, a steeper cognitive change was observed in the cognitive declines group. The correlation pattern between cognitive domains and functional outcomes differed between patients with and without cognitive declines. The present study characterized cognitive heterogeneity longitudinally in BD patients. As density of episodes play roles for cognitive declines, our results emphasize the importance of relapse prevention. Our findings provide hints for future personalized interventions and facilitating genetic and biological studies for dissecting the heterogeneity of bipolar illness.